COVID-19 stressors and mental health problems amongst women who arrived as refugees and those born in Australia. - Susan J Rees; Mohammed Mohsin; Alvin Kuowei Tay; Batool Moussa; Louis Klein; Nawal Nadar; Fatima Hussain; Yalini Krishna; Batoul Khalil; Mariam Yousif; Derrick Silove; Jane Fisher (Public Library of Science (PLoS), 2023)
Women from refugee background residing in high income countries are at greater mental health risk during the COVID-19 pandemic given their higher baseline prevalence of mental disorders, trauma exposures and social adversities. During the COVID-19 pandemic we drew on data from wave-4 of the WATCH cohort study, collected between October 2019 and June 2021. We conducted a cross-sectional analysis to compare the prevalence of common mental disorders (CMDs) from the sample of 650 consecutively recruited women, 339 (52.2%) from the refugee-background who were resettled in Australia and 311 (48.8%) randomly and contemporaneously selected Australian born women. We assessed COVID-19 psychosocial stressors: 1. COVID-related material hardship and 2. COVID-related fear and stress. We examined for associations between scores on these two items and CMDs in each group respectively. Compared to Australian-born woman, women from refugee background recorded a significantly higher prevalence of Major Depressive Disorder (MDD) (19.8% vs 13.5%), PTSD (9.7% vs 5.1%), Separation Anxiety Disorder (SEPAD) (19.8% vs 13.5%) and Persistent Complicated Bereavement Disorder (PCBD) (6.5% vs 2.9%). In refugee women, associations were found between COVID-related material hardship and CMDs [MDD, Relative Risk (RR) = 1.39, 95%CI: 1.02-1.89, p = 0.02] as well as between COVID-related fear and stress and CMDs (MDD, RR = 1.74, 95%CI: 1.04-2.90, p = 0.02 p = 0.02). For Australian-born women, associations were more commonly found between CMDs and material hardship. Our study demonstrates that both women from refugee background and those born in Australia are experiencing significant rates of CMD during the pandemic and that material hardship is an associated factor. We found that women from refugee background are at greater risk for mental health problems and are more likely to report an association of those problems with fear and stress related to COVID_19. All women, and particularly those from refugee background, require urgent and specialised attention to their mental health and psychosocial problems during this pandemic.